A Self‐Improved Water‐Oxidation Catalyst: Is One Site Really Enough?1. (20th November 2013) - López, Isidoro; Ertem, Mehmed Z.; Maji, Somnath; Benet‐Buchholz, Jordi; Keidel, Anke; Kuhlmann, Uwe; Hildebrandt, Peter; Cramer, Christopher J.; Batista, Victor S.; Llobet, Antoni
Abstract The homogeneous catalysis of water oxidation by transition‐metal complexes has experienced spectacular development over the last five years. Practical energy‐conversion schemes, however, require robust catalysts with large turnover frequencies. Herein we introduce a new oxidatively rugged and powerful dinuclear water‐oxidation catalyst that is generated by self‐assembly from a mononuclear catalyst during the catalytic process. Our kinetic and DFT computational analysis shows that two interconnected catalytic cycles coexist while the mononuclear system is slowly and irreversibly converted into the more stable dinuclear system: an extremely robust water‐oxidation catalyst that does not decompose over extended periods of time.